Konstruktionen und Konstruktionslernen

 Zeitschrift für Romanische Sprachen und ihre Didaktik

Phase Noise Investigation for a Radar System with Optical Clock Distribution - Kruse, Stephan; Bahmanian, Meysam; Kneuper, Pascal; Kress, Christian; Kurz, Heiko G.; Schneider, Thomas; Scheytt, Christoph (The 17th European Radar Conference)

Determination of Crystal-Field Splitting Induced by Thermal Oxidation of Titanium - Wojtaszek, Klaudia; Błachucki, Wojciech; Tyrała, Krzysztof; Nowakowski, Michał; Zaja̧c, Marcin; Stȩpień, Joanna; Jagodziński, Paweł; Banaś, Dariusz; Stańczyk, Wiktoria; Czapla-Masztafiak, Joanna; Kwiatek, Wojciech M.; Szlachetko, Jakub; et al. (The Journal of Physical Chemistry A)
Keywords: Physical and Theoretical Chemistry

Comparing the Effects of a Different Social Partner (Social Robot vs. Human) on Children's Social Referencing in Interaction - Tolksdorf, Nils F.; Crawshaw, Camilla E.; Rohlfing, Katharina (Frontiers in Education)
Social robots have emerged as a new digital technology that is increasingly being implemented in the educational landscape. While social robots could be deployed to assist young children with their learning in a variety of different ways, the typical approach in educational practices is to supplement the learning process rather than to replace the human caregiver, e.g., the teacher, parent, educator or therapist. When functioning in the role of an educational assistant, social robots will likely constitute a part of a triadic interaction with the child and the human caregiver. Surprisingly, there is little research that systematically investigates the role of the caregiver by examining the ways in which children involve or check in with them during their interaction with another partner — a phenomenon that is known as social referencing. In the present study, we investigated social referencing in the context of a dyadic child–robot interaction. Over the course of four sessions within our longitudinal language-learning study, we observed how 20 pre-school children aged 4–5 years checked in with their accompanying caregivers who were not actively involved in the language-learning procedure. The children participating in the study were randomly assigned to either an interaction with a social robot or a human partner. Our results revealed that all children across both conditions utilized social referencing behaviors to address their caregiver. However, we found that the children who interacted with the social robot did so significantly more frequently in each of the four sessions than those who interacted with the human partner. Further analyses showed that no significant change in their behavior over the course of the sessions could be observed. Findings are discussed with regard to the caregiver's role during children's interactions with social robots and the implications for future interaction design.
Keywords: Education

Progressive Reduction of Iconic Gestures Contributes to School-Aged Children’s Increased Word Production - Rohlfing, Katharina; Mertens, Ulrich (Frontiers in Psychology)

Do Shy Preschoolers Interact Differently When Learning Language With a Social Robot? An Analysis of Interactional Behavior and Word Learning - Tolksdorf, Nils Frederik; Viertel, Franziska E.; Rohlfing, Katharina J. (Frontiers in Robotics and AI)
Temperamental traits can decisively influence how children enter into social interaction with their environment. Yet, in the field of child–robot interaction, little is known about how individual differences such as shyness impact on how children interact with social robots in educational settings. The present study systematically assessed the temperament of 28 preschool children aged 4–5 years in order to investigate the role of shyness within a dyadic child–robot interaction. Over the course of four consecutive sessions, we observed how shy compared to nonshy children interacted with a social robot during a word-learning educational setting and how shyness influenced children’s learning outcomes. Overall, results suggested that shy children not only interacted differently with a robot compared to nonshy children, but also changed their behavior over the course of the sessions. Critically, shy children interacted less expressively with the robot in general. With regard to children’s language learning outcomes, shy children scored lower on an initial posttest, but were able to close this gap on a later test, resulting in all children retrieving the learned words on a similar level. When intertest learning gain was considered, regression analyses even confirmed a positive predictive role of shyness on language learning gains. Findings are discussed with regard to the role of shyness in educational settings with social robots and the implications for future interaction design.

Wurzel - Heidgen, Michael (Metzler Lexikon literarischer Symbole)

This is my Fight Song - Uppenkamp, Vera; Neumann, Anna; Kammeyer, Katharina (Musik als Lebensmittel. Kulturwissenschaftlich-theologische Rationen für ein Jahr)

"Wenn sich die Mitte auflöst...", ist das kein Verlust für die Religionspädagogik - ein bilanzierender Tagungsrückblick mit Augenzwinkern - Uppenkamp, Vera; Höger, Christian (Theo-Web. Zeitschrift für Religionspädagogik)

Art. Mädchen/Frauen - Uppenkamp, Vera (Das wissenschaftlich-religionspädagogische Lexikon im Internet www.wirelex.de)

"Gib mir was zu trinken, ich habe Durst..." Laientheologie nach Harald Schroeter-Wittke bei den Toten Hosen - Pinsch, Jan Christian (Musik als Lebensmittel. Kulturwissenschaftlich-theologische Rationen für ein Jahr)

Rezension zu Oliver Arnold, „Entjudung“ von Theologie und Kirche. Das Eisenacher „Institut zur Erforschung und Beseitigung des jüdischen Einflusses“ auf das deutsche kirchliche Leben 1939-1945, Bd. 6 Christentum und Zeitgeschichte, Leipzig 2020 - Pinsch, Jan Christian; Lerke, Stephanie (Paderborner Historische Mitteilungen)

Viel Lärm um die Stille. Die Geschichte des Raums der Stille an der Universität Paderborn im Spannungsfeld zwischen Religionsfreiheit und weltanschaulicher Neutralität - Pinsch, Jan Christian (Paderborner Historische Mitteilungen)

'Keine Gefangenen' oder 'Hyper Hyper' - Kommunikationen, Medien und Kulturen als Motoren gesellschaftlicher Transformationen. - Jacke, Christoph (Medienkultur als kritische Gesellschaftsanalyse. Festschrift für Rainer Winter.)

‚Deutsche’ Pop-Rezeption – zwischen journalistischen Trivialitäten und nationalen Eigenarten? - Jacke, Christoph (Gehört „deutsche“ Popmusik ins Museum? Materialien zu und von der Fünften Pop-Dekadentagung)

Ethische Bildung und inklusionsorientierter Religionsunterricht - Kammeyer, Katharina (Handbuch ethische Bildung. Religionspädagogische Fokussierungen)

This is my Fight Song - Kammeyer, Katharina; Neumann, Anna; Uppenkamp, Vera (Musik als Lebensmittel. Kulturwissenschaftlich-theologische Rationen für ein Jahr)

Improved non-linear devices for quantum applications - Gil López, Jano; Santandrea, Matteo; Roland, Ganaël; Brecht, Benjamin; Eigner, Christof; Ricken, Raimund; Quiring, Viktor; Silberhorn, Christine (New Journal of Physics)

Universal compressive tomography in the time-frequency domain - Gil López, Jano; Teo, Yong Siah; De, Syamsundar; Brecht, Benjamin; Jeong, Hyunseok; Silberhorn, Christine; Sánchez-Soto, Luis L. (Optica)

Musik und Sprache in Schauspielmusiken des 19. Jahrhunderts - Tumat, Antje

Learning to play golf for elderly people with subjective memory complaints: feasibility of a single‐blinded randomized pilot trial - Stroehlein, Julia K.; Vieluf, Solveig; Zimmer, Philipp; Schenk, Alexander; Oberste, Max; Gölz, Christian Johannes; van den Bongard, Franziska; Reinsberger, Claus (BMC Neurology)
Abstract Background Subjective Memory Complaints (SMC) in elderly people due to preclinical Alzheimer’s Disease may be associated with dysregulation of the Kynurenine Pathway (KP), with an increase in neurotoxic metabolites that affect cognition. Golf is a challenging sport with high demands on motor, sensory, and cognitive abilities, which might bear the potential to attenuate the pathological changes of preclinical AD. This trial investigated the feasibility of learning to play golf for elderly with cognitive problems and its effects on cognitive functions and the KP. Methods In a 22-week single-blinded randomized controlled trial, elderly people with SMC were allocated to the golf ( n = 25, 180 min training/week) or control group ( n = 21). Primary outcomes were feasibility (golf exam, adherence, adverse events) and general cognitive function (Alzheimer’s Disease Assessment Scale). Secondary outcomes include specific cognitive functions (Response Inhibition, Corsi Block Tapping Test, Trail Making Test), KP metabolites and physical performance (6-Minute-Walk-Test). Baseline-adjusted Analysis-of-Covariance was conducted for each outcome. Results 42 participants were analyzed. All participants that underwent the golf exam after the intervention passed it (20/23). Attendance rate of the golf intervention was 75 %. No adverse events or drop-outs related to the intervention occurred. A significant time*group interaction ( p = 0.012, F = 7.050, Cohen’s d = 0.89) was found for correct responses on the Response Inhibition task, but not for ADAS-Cog. Moreover, a significant time*group interaction for Quinolinic acid to Tryptophan ratios ( p = 0.022, F = 5.769, Cohen’s d = 0.84) in favor of the golf group was observed. An uncorrected negative correlation between attendance rate and delta Quinolinic acid to Kynurenic acid ratios in the golf group ( p = 0.039, r =-0.443) was found as well. Conclusions The findings indicate that learning golf is feasible and safe for elderly people with cognitive problems. Preliminary results suggest positive effects on attention and the KP. To explore the whole potential of golfing and its effect on cognitive decline, a larger cohort should be studied over a longer period with higher cardiovascular demands. Trial registration The trial was retrospectively registered (2nd July 2018) at the German Clinical Trials Register ( DRKS00014921 ).
Keywords: Clinical Neurology; General Medicine

Generalized tonic-clonic seizures are accompanied by changes of interrelations within the autonomic nervous system. - Vieluf, S; Hasija, Tanuj; Schreier, PJ; El Atrache, R; Hammond, S; Mohammadpour Touserkani, F; Sarkis, RA; Loddenkemper, T; Reinsberger, Claus (Epilepsy Behav)

Electrophysiological signatures of dedifferentiation differ between fit and less fit older adults - Gölz, Christian Johannes; Mora, Karin; Stroehlein, Julia Kristin; Haase, Franziska Katharina; Dellnitz, Michael; Reinsberger, Claus; Vieluf, Solveig (Cognitive Neurodynamics)
Abstract Cardiorespiratory fitness was found to influence age-related changes of resting state brain network organization. However, the influence on dedifferentiated involvement of wider and more unspecialized brain regions during task completion is barely understood. We analyzed EEG data recorded during rest and different tasks (sensory, motor, cognitive) with dynamic mode decomposition, which accounts for topological characteristics as well as temporal dynamics of brain networks. As a main feature the dominant spatio-temporal EEG pattern was extracted in multiple frequency bands per participant. To deduce a pattern’s stability, we calculated its proportion of total variance among all activation patterns over time for each task. By comparing fit (N = 15) and less fit older adults (N = 16) characterized by their performance on a 6-min walking test, we found signs of a lower task specificity of the obtained network features for the less fit compared to the fit group. This was indicated by fewer significant differences between tasks in the theta and high beta frequency band in the less fit group. Repeated measures ANOVA revealed that a significantly lower proportion of total variance can be explained by the main pattern in high beta frequency range for the less fit compared to the fit group [F(1,29) = 12.572, p = .001, partial η 2 = .300]. Our results indicate that the dedifferentiation in task-related brain activation is lower in fit compared to less fit older adults. Thus, our study supports the idea that cardiorespiratory fitness influences task-related brain network organization in different task domains.
Keywords: Cognitive Neuroscience

Classification of visuomotor tasks based on electroencephalographic data depends on age-related differences in brain activity patterns - Gölz, Christian Johannes; Mora, K.; Rudisch, J.; Gaidai, Roman; Reuter, E.; Godde, B.; Reinsberger, Claus; Voelcker-Rehage, C.; Vieluf, S. (Neural Networks)
Keywords: Artificial Intelligence; Cognitive Neuroscience

Thermostable water reservoirs in the interlayer space of a sodium hectorite clay through the intercalation of γ-aminopropyl(dimethyl)ethoxysilane in toluene - Keil, Waldemar; Zhao, Kai; Oswald, Arthur; Bremser, Wolfgang; Schmidt, Claudia; Hintze-Bruening, Horst (Physical Chemistry Chemical Physics)
Thermostable compartmentalized sodium-water sites through intercalated γ-aminopropyl-dimethyl-ethoxy silane in synthetic hectorite.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Mechanism and equilibrium thermodynamics of H- and J-aggregate formation from pseudo isocyanine chloride in water - Hämisch, Benjamin; Huber, Klaus (Soft Matter)
Pseudo isocyanine chloride monomers equilibrate with H-oligomers and, separated by a threshold, with H-oligomers and fiber-like J-aggregates. The mechanism and thermodynamics of J-aggregate formation is interpreted with the concept of chain growth.
Keywords: Condensed Matter Physics; General Chemistry

Self-Assembled Fibrinogen Hydro- and Aerogels with Fibrin-like 3D Structures - Hense, Dominik; Büngeler, Anne; Kollmann, Fabian; Hanke, Marcel; Orive, Alejandro; Keller, Adrian; Grundmeier, Guido; Huber, Klaus; Strube, Oliver I. (Biomacromolecules)
Keywords: Materials Chemistry; Polymers and Plastics; Biomaterials; Bioengineering

Multiresponsive Polymer Nanoparticles Based on Disulfide Bonds - Wagner, Maximilian; Krieger, Anja; Minameyer, Martin; Hämisch, Benjamin; Huber, Klaus; Drewello, Thomas; Gröhn, Franziska (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Thermodynamic Analysis of the Self‐Assembly of Pseudo Isocyanine Chloride in the Presence of Crowding Agents - Hämisch, Benjamin; Pollak, Roland; Ebbinghaus, Simon; Huber, Klaus (ChemSystemsChem)
Keywords: General Earth and Planetary Sciences; General Environmental Science

Classification of visuomotor tasks based on electroencephalographic data depends on age-related differences in brain activity patterns - Goelz, C.; Mora, K.; Rudisch, J.; Gaidai, R.; Reuter, E.; Godde, B.; Reinsberger, Claus; Voelcker-Rehage, C.; Vieluf, S. (Neural Networks)
Keywords: Artificial Intelligence; Cognitive Neuroscience

Twenty-four-hour patterns in electrodermal activity recordings of patients with and without epileptic seizures. - Vieluf, S; Amengual-Gual, M; Zhang, B; El Atrache, R; Ufongene, C; Jackson, MC; Branch, S; Reinsberger, Claus; Loddenkemper, T (Epilepsia)

Exercise and sports after COVID-19-Guidance from a clinical perspective. - Halle, M; Bloch, W; Niess, AM; Predel, HG; Reinsberger, Claus; Scharhag, J; Steinacker, J; Wolfarth, B; Scherr, J; Niebauer, J (Transl Sports Med)

The effects of repetitive head impacts on postural control: A systematic review. - Bonke, EM; Southard, J; Buckley, TA; Reinsberger, Claus; Koerte, IK; Howell, DR (J Sci Med Sport)

Head injuries in professional football (soccer): Results of video analysis verified by an accident insurance registry. - Krutsch, V; Krutsch, W; Härtl, J; Bloch, H; Alt, V; Klein, C; Reinsberger, Claus; Seiffert, R; Huber, L; Weber, J (PLoS One)

Evaluation of Open-Source and Pre-Trained Deep Convolutional Neural Networks Suitable for Player Detection and Motion Analysis in Squash. - Brumann, C; Kukuk, M; Reinsberger, Claus (Sensors (Basel))

Zunftbankett und Göttermahl – Mahlzeiten im Leben und Werk niederländischer Maler im 16. Jahrhundert. Ansätze zur Interpretation - Harnack, Maria (Paderborner Historische Mitteilungen)

Afrikanische Masken und Skulpturen der Sammlung Karl-Josef Scheideler des Lippischen Landesmuseums Detmold - Duschner, Paul

Spuren des Kolonialismus in der Airport Art: Vier Beispiele aus Westfalen - Duschner, Paul (Koloniale Welten in Westfalen)

Entwicklung einer Methode zur differenzierten Messung des Wachstums der Rissenden von Innenrissen mit der Elektropotentialmethode - Kullmer, Gunter; Weiß, Deborah; Schramm, Britta

Effektivität von Luftreinigern zur Reduzierung des COVID-19-Infektionsrisikos/ Efficacy of air purifiers in reducing the risk of COVID-19 infections - Schumacher, Stefan; Asbach, Christof; Schmid, Hans-Joachim (Gefahrstoffe)
Luftreiniger werden derzeit häufig als mögliches Hilfsmittel zur Minimierung des Infektionsrisikos im Rahmen der COVID-19-Pandemie diskutiert. Dabei taucht oft die Frage auf, ob Luftreiniger grundsätzlich in der Lage sind, Viren oder virenbeladene Tröpfchen abzuscheiden. Ziel dieses Artikels ist es, die wesentlichen Grundlagen der Wirkungsweise von Luftreinigern und Filtern zu beschreiben, Methoden zur Messung der Reinigungswirkung im Größenbereich von Viren und virenbeladenen Tröpfchen aufzuzeigen sowie typische Szenarien zum Betrieb von Luftreinigern in einem mathematischen Modell zu erfassen. Darauf basierend können die Möglichkeiten und Grenzen von Luftreinigern für reale Anwendungsfälle besser eingeschätzt werden.

Einleitung – Introduction - Seng, Eva- Maria; Göttmann, Frank (Innovation in der Bauwirtschaft – Innovation in the building industry. Wesersandstein vom 16. bis 19. Jahrhundert – Weser Sandstone form the 16th to the 19th Century)

Authentizität und kulturelles Erbe – Genese, Aufnahme und Diskussion des Authentizitätsaspektes in die Welterbekonvention - Seng, Eva- Maria (Weitergabe und Wiedergabe. Dimensionen des Authentischen im Umgang mit immateriellem Kulturerbe)

Innovation in der Bauwirtschaft – Innovation in the building industry. Wesersandstein vom 16. bis 19. Jahrhundert – Weser Sandstone form the 16th to the 19th Century

Otto Bartning, Spektakuläre Kirchenbaulösungen versus Einfachbauten - Seng, Eva- Maria (Protestantische Impulse. Prägende Gestalten in Deutschland nach 1945)

Erkundungen in die Kunstgeschichte, Kirchenbau, Städtebau, Utopie, Sammelband von bislang meist unpublizierten Aufsätzen - Seng, Eva- Maria

Ein Beitrag zur Entwicklung einer additiv gefertigten Unterschenkelorthese unter Berücksichtigung biomechanischer Aspekte des Charcot-Fußes - Schafran, Tommy

Methodenentwicklung zur numerischen Lebensdauerprognose von hyperelastischen Klebverbindungen infolge zyklischer Beanspruchung mittels bruchmechanischer Ansätze - Tews, Karina; Aubel, Tobias; Teutenberg, Dominik; Meschut, Gerson; Duffe, Tobias; Kullmer, Gunter (DECHEMA, Gesellschaft für Chemische Technik und Biotechnologie e.V. (Ed.), 21. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Application of engineering methods in the planning process of surgical treatments - Risse, Lena; Kullmer, Gunter (Journal of 3D Printing in Medicine)
The continuous development of medical methods in recent decades has achieved measurable improvement. The interdisciplinary cooperation of engineers and physicians is a forward-looking component of this development. However, this cooperation also results in new interfaces on the communication and software level, which must be defined by implementing a systematic workflow. In this paper, the step-by-step implementation of engineering methods into the surgical workflow is shown. The focus is on the basic requirements and the necessary exchange of information. Additively manufactured models for preoperative elucidation of the patient are used as a psychological added value to increase the transparency of the surgical procedure. In addition, the models serve to train young surgeons and provide the opportunity to plan advanced surgical techniques.
Keywords: General Medicine

Experimentelle Ermittlung von Rissfortschrittskurven für hyperelastische Klebstoffe - Duffe, Tobias; Schramm, Britta; Kullmer, Gunter

Bruchmechanische Lebensdauervorhersage für hyperelastische Klebverbindungen - Duffe, Tobias; Kullmer, Gunter; Tews, Karina; Aubel, Tobias; Meschut, Gerson (51. DVM-Tagung, Arbeitskreis Bruchmechanik und Bauteilsicherung)

Local Power Control using Wireless Sensor System for Microgrids in Africa - Hilleringmann, Ulrich; Petrov, Dmitry; Mwammenywa, Ibrahim; Kagarura, Geoffrey M.
Keywords: Art-D; Afrika

Frequency-Doubler Modulation for Reduced Junction Temperatures for LLC Resonant Converters Operated in Half-Bridge Configuration - Rehlaender, Philipp; Unruh, Roland; Hankeln, Lars; Schafmeister, Frank; Böcker, Joachim (23rd European Conference on Power Electronics and Applications (EPE'21 ECCE Europe))
LLC resonant converters are typically unsuitable to be applied for wide voltage-transfer ratio applications. With a full-bridge inverter, however, they can be operated in a variety of different modulations. Most notably, by permanently turning on one MOSFET and turning off the other MOSFET of the same bridge leg, the LLC can be operated in half-bridge configuration reducing the gain by a factor of two. The resonant capacitor is hereby charged to an average voltage of half the input voltage. In this modulation, however, the switch that is permanently turned on is stressed by the complete resonant current while exhibiting no switching losses. This paper proves that the frequency-doubler modulation can better balance the losses among all MOSFETs and should be the preferred mode of operation favored over the conventional half-bridge modulation. This paper analyzes the beneficial loss distribution, proposes an on-the-fly morphing modulation and discusses potential operating strategies to further reduce the junction temperature. Furthermore, it is shown that this modulation can also be altered to achieve the asymmetrical LLC operation. Experimental measurement results show that the modulation results in a substantial decrease of the maximum MOSFET temperature and shows that the converter can be smoothly transitioned during operation from full-bridge modulation to the frequency-doubler half-bridge operation and back.
Keywords: Resonant converter; High frequency power converter; Switched-mode power supply; Converter control; Control methods for electrical systems

Zwei-Rollen-Gießwalzen und thermomechanische Behandlung von dünnen Bändern aus der Aluminiumlegierung EN AW-6082 - Stolbchenko, Mykhailo

Steady states of $Λ$-type three-level systems excited by quantum light in lossy cavities - Rose, H.; Tikhonova, O. V.; Meier, T.; Sharapova, P. (arXiv:2109.00842)
The interaction between quantum light and matter is being intensively studied for systems that are enclosed in high-$Q$ cavities which strongly enhance the light-matter coupling. However, for many applications, cavities with lower $Q$-factors are preferred due to the increased spectral width of the cavity mode. Here, we investigate the interaction between quantum light and matter represented by a $Λ$-type three-level system in lossy cavities, assuming that cavity losses are the dominant loss mechanism. We demonstrate that cavity losses lead to non-trivial steady states of the electronic occupations that can be controlled by the loss rate and the initial statistics of the quantum fields. The mechanism of formation of such steady states can be understood on the basis of the equations of motion. Analytical expressions for steady states and their numerical simulations are presented and discussed.

Spectrally multimode integrated SU(1,1) interferometer - Ferreri, Alessandro; Santandrea, Matteo; Stefszky, Michael; Luo, Kai Hong; Herrmann, Harald; Silberhorn, Christine; Sharapova, Polina R. (Quantum)
Nonlinear SU(1,1) interferometers are fruitful and promising tools for spectral engineering and precise measurements with phase sensitivity below the classical bound. Such interferometers have been successfully realized in bulk and fiber-based configurations. However, rapidly developing integrated technologies provide higher efficiencies, smaller footprints, and pave the way to quantum-enhanced on-chip interferometry. In this work, we theoretically realised an integrated architecture of the multimode SU(1,1) interferometer which can be applied to various integrated platforms. The presented interferometer includes a polarization converter between two photon sources and utilizes a continuous-wave (CW) pump. Based on the potassium titanyl phosphate (KTP) platform, we show that this configuration results in almost perfect destructive interference at the output and supersensitivity regions below the classical limit. In addition, we discuss the fundamental difference between single-mode and highly multimode SU(1,1) interferometers in the properties of phase sensitivity and its limits. Finally, we explore how to improve the phase sensitivity by filtering the output radiation and using different seeding states in different modes with various detection strategies.

Managing spectral properties and Schmidt mode content of squeezed vacuum light using sum-frequency converter - Sukharnikov, Vladislav; Sharapova, Polina; Tikhonova, Olga (Optics & Laser Technology)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Komplexe Wörter richtig schreiben. Wortanalyse als Rechtschreibstrategie. - Lang, Susanne; Topalović, Elvira (In: Praxis Deutschunterricht)

Rechtschreibstrategien und Sprachstrukturen. - Noack, Christina; Topalović, Elvira (In: Praxis Deutschunterricht)

Reconfigurable quantum photonics with on-chip detectors - Gyger, S; Zichi, J; Schweickert, L; Elshaari, A.W; Steinhauer, S; Covre da Silva, S.F; Rastelli, A; Zwiller, V; Jöns, Klaus D.; Errando-Herranz, C

Engineering the Luminescence and Generation of Individual Defect Emitters in Atomically Thin MoS2 - Klein, J; Sigl, L; Gyger, S; Barthelmi, K; Florian, M; Rey, S; Taniguchi, T; Watanabe, K; Jahnke, F; Kastl, C; Zwiller, V; Jöns, Klaus D.; et al.

Quantum Teleportation with Imperfect Quantum Dots - Basso Basset, F; Salusti, F; Schweickert, L; Rota, M.B; Tedeschi, D; Covre da Silva, S.F; Roccia, E; Zwiller, V; Jöns, Klaus D.; Rastelli, A; Trotta, R

Quantum dots as potential sources of strongly entangled photons: Perspectives and challenges for applications in quantum networks - Schimpf, C; Reindl, M; Basset, F.B; Jöns, Klaus D.; Trotta, R; Rastelli, A

Gate-Switchable Arrays of Quantum Light Emitters in Contacted Monolayer MoS2 van der Waals Heterodevices - Hötger, A; Klein, J; Barthelmi, K; Sigl, L; Sigger, F; Männer, W; Gyger, S; Florian, M; Lorke, M; Jahnke, F; Taniguchi, T; Watanabe, K; et al.

Quantum dot technology for quantum repeaters: from entangled photon generation toward the integration with quantum memories - Neuwirth, J; Basso Basset, F; Rota, M. B; Roccia, E; Schimpf, C; Jöns, Klaus D.; Rastelli, A; Trotta, R

Strain-Controlled Quantum Dot Fine Structure for Entangled Photon Generation at 1550 nm - Lettner, T; Gyger, S; Zeuner, K.D; Schweickert, L; Steinhauer, S; Hedlund, C. Reuterskiöld; Stroj, S; Rastelli, A; Hammar, M; Trotta, R; Jöns, Klaus D; Zwiller, V

Integrated photon-pair sources with nonlinear optics - Wang, Y; Jöns, Klaus D.; Sun, Z

Telecom-wavelength InAs QDs with low fine structure splitting grown by droplet epitaxy on GaAs (111) A vicinal substrates - Tuktamyshev, A; Fedorov, A; Bietti, S; Vichi, S; Zeuner, K.D; Jöns, Klaus D.; Chrastina, D; Tsukamoto, S; Zwiller, V; Gurioli, M; Sanguinetti, S

Resonance fluorescence from waveguide–coupled, strain–localized two–dimensional quantum emitters - Errando-Herranz, C; Schöll, E; Picard, R; Laini, M; Gyger, S; Elshaari, A.W; Branny, A; Wennberg, U; Barbat, S; Renaud, T; Brotons-Gisbert, M; Bonato, C; et al.

On-Demand Generation of Entangled Photon Pairs in the Telecom C-Band with InAs Quantum Dots - Jöns, Klaus D.; Zeuner, K.D; Schweickert, L; Hedlund, C.R; Lobato, C.N; Lettner, T; Wang, K; Gyger, S; Schöll, E; Steinhauer, S; Hammar, M; Zwiller, V

Experimentelle bruchmechanische Untersuchung eines clinchgeeigneten Bleches aus HCT590X mithilfe einer neuen Probengeometrie - Weiß, Deborah; Schramm, Britta; Neuser, Moritz; Grydin, Olexandr; Kullmer, Gunter

Effizienzsteigerung von Haushaltskühlgeräten durch polymergebundene Phasenwechselmaterialien - Sonnenrein, Gerrit

Systemtheorie von Hardware-in-the-Loop-Simulationen mit Anwendung auf einem Fahrzeugachsprüfstand mit parallelkinematischem Lastsimulator - Olma, Simon

Systematik zur Evolution technischer Anforderungen - Lankeit, Christopher

Angehende (Religions-)Lehrkräfte begleiten aber wie?

Das Audioviduum. Eine Theoriegeschichte des Menschenmotivs in audiovisuellen Medien - Eckel, Julia

Islamischer Religionsunterricht. Beitrag zu einem friedlichen Zusammenleben - Elshahawy, Ahmed

The multiplicity of halal standards: a case study of application to slaughterhouses - Abdelrahem, Mohammed; Abdallah, Ali; Pasqualone, Antonella (Journal of Ethnic Foods)

Modellbasierte Synthese einer hybriden Kraft-/Positionsregelung für einen Fahrzeugachsprüfstand mit hydraulischem Hexapod - Kohlstedt, Andreas

W. M. Ormrod: Women and Parliament in Later Medieval England (The New Middle Ages) - Foerster, Anne (H-Soz-Kult)

Rissverhalten von unidirektionalen Flachsfaser-Epoxidharz-Verbunden infolge statischer Belastung - Keck, Stefan

„Power Poses“ – Fakten, frisierte Daten, Forschungslyrik? Ein Unterrichtsvorhaben zu Praktiken und Darstellungsformen psychologischer Forschung am Beispiel von nonverbaler Kommunikation - Schreiber, Christine; Scharlau, Ingrid; Patrzek, Justine (Psychologieunterricht)
Keywords: Unterrichtsfach Psychologie

Unterrichtsfach Psychologie an der Universität Paderborn - Patrzek, Justine; Buhl, Heike M.; Scharlau, Ingrid (Psychologieunterricht)
Keywords: Unterrichtsfach Psychologie

PIVOT: A Parsimonious End-to-End Learning Framework for Valuing Player Actions in Handball using Tracking Data - Müller, Oliver; Caron, Matthew; Döring, Michael; Heuwinkel, Tim; Baumeister, Jochen (8th Workshop on Machine Learning and Data Mining for Sports Analytics (ECML PKDD 2021))
Over the last years, several approaches for the data-driven estimation of expected possession value (EPV) in basketball and association football (soccer) have been proposed. In this paper, we develop and evaluate PIVOT: the first such framework for team handball. Accounting for the fast-paced, dynamic nature and relative data scarcity of hand- ball, we propose a parsimonious end-to-end deep learning architecture that relies solely on tracking data. This efficient approach is capable of predicting the probability that a team will score within the near future given the fine-grained spatio-temporal distribution of all players and the ball over the last seconds of the game. Our experiments indicate that PIVOT is able to produce accurate and calibrated probability estimates, even when trained on a relatively small dataset. We also showcase two interactive applications of PIVOT for valuing actual and counterfactual player decisions and actions in real-time.
Keywords: expected possession value; handball; tracking data; time series classification; deep learning

To the Moon! Analyzing the Community of “Degenerates” Engaged in the Surge of the GME Stock - Caron, Matthew; Gulenko, Maryna; Müller, Oliver (42nd International Conference on Information Systems (ICIS 2021))
In early 2021, the finance world was taken by storm by the dramatic price surge of the GameStop Corp. stock. This rise is being, at least in part, attributed to a group of Redditors belonging to the now-famous r/wallstreetbets (WSB) subreddit group. In this work, we set out to address if user activity on the WSB subreddit is associated with the trading volume of the GME stock. Leveraging a unique dataset containing more than 4.9 million WSB posts and comments, we assert that user activity is associated with the trading volume of the GameStop stock. We further show that posts have a significantly higher predictive power than comments and are especially helpful for predicting unusually high trading volume. Lastly, as recent events have shown, we believe that these findings have implications for retail and institutional investors, trading platforms, and policymakers, as these can have disruptive potential.
Keywords: Retail investors; GameStop; Social Networks; Reddit; WallStreetBets

Towards Quantum One-Time Memories from Stateless Hardware - Broadbent, Anne; Gharibian, Sevag; Zhou, Hong-Sheng (Quantum)
A central tenet of theoretical cryptography is the study of the minimal assumptions required to implement a given cryptographic primitive. One such primitive is the one-time memory (OTM), introduced by Goldwasser, Kalai, and Rothblum [CRYPTO 2008], which is a classical functionality modeled after a non-interactive 1-out-of-2 oblivious transfer, and which is complete for one-time classical and quantum programs. It is known that secure OTMs do not exist in the standard model in both the classical and quantum settings. Here, we propose a scheme for using quantum information, together with the assumption of stateless (i.e., reusable) hardware tokens, to build statistically secure OTMs. Via the semidefinite programming-based quantum games framework of Gutoski and Watrous [STOC 2007], we prove security for a malicious receiver making at most 0.114n adaptive queries to the token (for n the key size), in the quantum universal composability framework, but leave open the question of security against a polynomial amount of queries. Compared to alternative schemes derived from the literature on quantum money, our scheme is technologically simple since it is of the "prepare-and-measure" type. We also give two impossibility results showing certain assumptions in our scheme cannot be relaxed.
Keywords: Physics and Astronomy (miscellaneous); Atomic and Molecular Physics; and Optics

The Public Service Media and Public Service Internet Utopias Survey Report - Fuchs, Christian (The Public Service Media and Public Service Internet Manifesto)

Communicating COVID-19. Everyday Life, Digital Capitalism, and Conspiracy Theories in Pandemic Times. SocietyNow Series - Fuchs, Christian

History and Class Consciousness 2.0: Georg Lukács in the Age of Digital Capitalism and Big Data - Fuchs, Christian (Information, Communication and Society)

Marxist Humanism and Communication Theory. Media, Communication and Society Volume One - Fuchs, Christian

Engels@200: Friedrich Engels and Digital Capitalism. How Relevant Are Engels’s Works 200 Years After His Birth? - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Engels@200: Friedrich Engels in the Age of Digital Capitalism. Introduction - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Cornel West and Marxist Humanism - Fuchs, Christian (Critical Sociology)

Das digitale Kapital. Zur Kritik der politischen Ökonomie des 21. Jahrhunderts - Fuchs, Christian

The Public Service Media and Public Service Internet Manifesto

Social Media: A Critical Introduction. Third English edition - Fuchs, Christian

The Future of Public Service Media and the Internet - Alessandro, D'Arma; Fuchs, Christian; Horowitz, Minna; Unterberger, Klaus (The Public Service Media and Public Service Internet Manifesto)

Introduction - Fuchs, Christian; Unterberger, Klaus (The Public Service Media and Public Service Internet Manifesto)

The Digital Commons and the Digital Public Sphere: How to Advance Digital Democracy Today - Fuchs, Christian (Westminster Papers in Communication and Culture)

How Did Donald Trump Incite a Coup Attempt? - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)